PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA SEKOLAH DASAR UNTUK MENUMBUHKEMBANGKAN JIWA KEWIRAUSAHAAN - Hery Kristanto, Vigih (Widya Warta, 2012)
Today, many highly educated members of society actually become unemployed. This is one of the problems of education in Indonesia. This phenomenon will not occur if at every level of education there is guidance to foster an entrepreneurial spirit. To formulate a curriculum that contains entrepreneurial training in mathematics learning is certainly not easy. Related to this, the effort for it can be initiated by developing the instruments of mathematics learning which include training to foster entrepreneurial spirit and utilize the existing model. To develop the learning instruments requires development strategies. In this discussion, one of the alternative strategies to develop learning instruments is Borg and Gall’s development strategy. This development strategy combines with Nieven’s criteria fordevelopment of teaching materials, namely: valid, practical, and effective. Thus, if all the learning instruments which include Learning Implementation Plan (LIP), Guidebook for Teacher (GFT), Student Book (SB), Student Worksheet (SW), and Test of Learning Outcomes (TLO) have meet Nieven’s criteria, then the learning instruments are ready to be used and disseminated.